Analysis Method and Application of the Degree of Freedom and Mobility of a Kind of Complex Planar Mechanism - Zhang Yan; Sun Qipeng; Deng Aoran; Qiu Lu; Li Gangyan (Jixie chuandong)
The screw theory is adopted to analyze the constraint of planar mechanisms branch link on mobile platform,the redundant constraint and partial degree of freedom of mechanism is found out,and the formula of degree of freedom is modified,the mobility of planar mechanisms is researched by analyzing constraints virtual power of mechanisms branch link,which can judge whether mechanism move continuously. The effectiveness of proposed method is verified by an example of a planar instantaneous motion mechanism. Finally,taking a radar vehicle-borne array lifting mechanism as research object,the results show that the analysis method of the degree of freedom and mobility is suitable for complex planar mechanisms which contain redundant constraint.